Adsorptive properties and on-demand magnetic response of lignin@Fe3O4 nanoparticles at castor oil–water interfaces. Issue 5 (19th January 2023) - Hasan, Mohammad Jahid; Westphal, Emily; Chen, Peng; Saini, Abhishek; Chu, I-Wei; Watzman, Sarah J.; Ureña-Benavides, Esteban; Vasquez, Erick S.
Abstract : Lignin@Fe3 O4 nanoparticles adsorb at oil–water interfaces, form Pickering emulsions, induce on-demand magnetic responses to break emulsions, and can sequester oil from water. Abstract : Lignin@Fe3 O4 nanoparticles adsorb at oil–water interfaces, form Pickering emulsions, induce on-demand magnetic responses to break emulsions, and can sequester oil from water. Lignin@Fe3 O4 nanoparticles were prepared using a pH-induced precipitation method and were fully characterized. These were used to prepare Pickering emulsions with castor oil/Sudan red G dye and water at various oil/water volume ratios and nanoparticle concentrations. The stability and demulsification of the emulsions under different magnetic fields generated with permanent magnets (0–540 mT) were investigated using microscopy images and by visual inspection over time. The results showed that the Pickering emulsions were more stable at the castor oil/water ratio of 50/50 and above. Increasing the concentration of lignin@Fe3 O4 improved the emulsion stability and demulsification rates with 540 mT applied magnetic field strength. The adsorption of lignin@Fe3 O4 nanoparticles at the oil/water interface using 1-pentanol evaporation through Marangoni effects was demonstrated, and magnetic manipulation of a lignin@Fe3 O4 stabilized castor oil spill in water was shown. Nanoparticle concentration and applied magnetic field strengths were analyzed for the recovery of spilled oil from water; it was observed that increasing the magnetic strength increased oil spill motion for a lignin@Fe3 O4 concentration of up to 0.8 mg mL −1 at 540 mT. Overall, this study demonstrates the potential of lignin-magnetite nanocomposites for rapid on-demand magnetic responses to externally induced stimuli.